Strategies for Handling Stunting in Nagan Raya Districts - Leni Fazila; Siti Maisyaroh Fitri Siregar; Fitrah Reynaldi; Arfah Husna (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
Stunting is when a person's height is less than average based on age and gender. This study aims to determine the strategy of the Nagan Raya Health Office in reducing stunting rates. This type of research used qualitative research. Data collection techniques are observation, interviews, and documentation. Research informants were the Head of the Health Service, Head of Public Health, Head of Family Health and Nutrition, Head of Promotion and Community Empowerment, Head of Environmental Health, Occupational Health, and Sports. Data analysis techniques are data reduction, data management, and concluding. The results showed that the Nagan Raya health department's strategy for reducing stunting rates was quite good. With eight integrated stunting reduction interventions, specific nutrition interventions, and sensitive nutrition interventions collaborated with cross-sectoral involvement. In conclusion, from 8 integrated stunting reduction interventions, the basis is stunting consultation. The obstacles are that it is difficult to use the budget for stunting, uniting stakeholders' perceptions, and the village government lacks knowledge. Supporting resources are sufficient, namely human resources (HR), facilities, and infrastructure, but it is still insufficient in terms of the budget. Suggestions that socialization is given to the village government. It is hoped that the Health Service and government organizations involved will remain consistent and unite their perceptions and maximize their budget.